The Crisis of Meaning: A Chestertonian Response - Reyburn, Duncan (Religions, 2025)
One of the main cultural achievements of modernity, according to Hartmut Rosa, is that it has nearly perfected “human beings’ ability to establish a certain distance from the world while at the same time bringing it within our manipulative reach”. Although this ‘achievement’ has ensured many remarkable scientific and technological developments, the consequences for culture have been more negative, often taking the form of what is often referred to as the malaise of modernity. Over time, this malaise has intensified to make way for what is now commonly known as the crisis of meaning, which pivots around the erosion of three orders of meaning, named and discussed by John Vervaeke: the nomological order, the narrative order, and the normative order. The work of G. K. Chesterton is consulted, in this article, to grapple with the deeper theological meaning of the modern malaise and the present crisis of meaning. In Chesterton’s work, it is better to interpret any cultural crisis, like the Edwardian cultural crisis he saw first-hand, as well as the current meaning crisis, through theology, and especially in relation to the doctrines of God’s goodness, the goodness of created order, and the doctrine of original sin, narrated as the fall of man. Through this, it becomes possible to better understand and articulate Chesterton’s theological mediation of culture as a more specific aspect of his larger hermeneutical awareness.